The Design of Security Framework for LoRaWAN FUOTA (Universitas Muhammadiyah Yogyakarta, 2023)
This research outlines a comprehensive security framework for LoRaWAN Firmware Updates Over-The-Air (FUOTA), which is essential for ensuring the reliability of IoT devices in critical infrastructures. It addresses multiple security threats specific to the wireless transmission of firmware updates, initiating an assessment of the vulnerabilities faced by the LoRaWAN FUOTA process. The framework incorporates several security measures, including secure transmission using lightweight encryption to maintain data confidentiality, robust authentication and authorization strategies to prevent unauthorized access, and digital signatures for integrity verification to ensure only authentic firmware updates are installed. It also includes anti-replay measures like sequence numbers and timestamps to protect against replay attacks and emphasizes efficient resource management to optimize power and computational resources for IoT devices. Additionally, secure multicast management techniques are employed to handle the challenges of simultaneously distributing updates to multiple devices. The framework provides an integrated and detailed approach to enhancing the security and operational efficiency of LoRaWAN FUOTA, making it an invaluable resource for practitioners and researchers in the field.